Position of witness in the judge power system in Indonesia - Yudo Adiananto; Abdul Rachmad Budiono; Tunggul Anshari SN; Iwan Permadi (Technium Social Sciences Journal, 2020)
The prosecutor’s position as a government agency that carries out state power in the field of prosecution has resulted in its own legal problems. The Attorney General’s Office, on the one hand, is part of a government agency (executive) and is carrying out a prosecution (judicial) function. There is a conflict of norms in the regulation between Article 2 paragraph (1) of Law No. 30 of 2004 concerning the Attorney General’s Office of the Republic of Indonesia with Article 38 paragraph (1) and paragraph (2) letter b of Law No. 48 of 209 concerning Judicial Power. The Prosecutor’s Office in carrying out its authority independently and independently in the field of prosecution is difficult to be separated from the influence of the power of the authorities, because the Prosecutor’s position is under the executive power.